Supramolecular Polymers With AIE Property Fabricated From a Cyanostilbene Motif-Derived Ditopic Benzo-21-Crown-7 and a Ditopic Dialkylammonium Salt - Wu, Haoran; Xiao, Tangxin (Frontiers in Chemistry, 2020)
Fluorescent supramolecular polymers (FSP) have attracted considerable attention in recent years. Particularly, the incorporation of aggregation-induced emission (AIE) property to the FSP will bring this material into practical applications. Herein, we designed and synthesized a cyanostilbene motif derived ditopic benzo-21-crown-7 (B21C7) as a host molecule (H). The cyanostilbene motif endows H with AIE property while the B21C7 motif renders it with the capability to complex with electron deficient guest molecules. Upon the addition of a ditopic dialkylammonium salt molecule (G), a novel FSP with blue luminescent property can be constructed. This B21C7-based host-guest FSP with blue fluorescence may have potential application in supramolecular luminescent materials.